Hubungan BBLR dengan Kejadian Stunting di Kelurahan Donan : Hubungan BBLR dengan Kejadian Stunting di Kelurahan Donan - Dhiah Dwi Kusumawati; Rochany Septiyaningsih; Susilawati Susilawati (Universitas Islam Jember, 2021)
Stunting is a condition of failure to thrive in children under five years of age as a result of chronic malnutrition so that children are too short for their age and have the risk of decreasing intellectual abilities and increasing the risk of degenerative diseases in the future. The purpose of this study was to determine the relationship between LBW and the incidence of stunting. The design of this study was case control with a population of all stunting toddlers (30 toddlers). This study used a total sampling method with a total of 30 cases and 30 controls. Data were collected by interview using a questionnaire and anthropometry to measure height. Data processing used univariate analysis and bivariate analysis. The results of the analysis concluded that there was a significant relationship between low birth weight (LBW) and the incidence of stunting in children under five in Donan Village. The Puskesmas should conduct regular classes for mothers of children under five and pregnant women. Key words: stunting; toddler; LBW